Community social responsibility and knowledge transfer: Cultivating innovation and improving economic levels for indigenous communities - Mohammed, Abdul Hapes; Abdul Rashid, Nur Firdaus; Ghazali, Mimi Diana; Mat Nazir, Eliy Nazira; Ismail, Noraini (Journal of Islamic, Social, Economics and Development, 2024)
This paper explores the impact of a community social responsibility (CSR) project focused on transferring knowledge to the indigenous community of Kg Beswok, Pos Yum Sg. Siput, Perak. The project emphasizes the production of soap from wasted cooking oil, aiming to foster innovation and enhance the economic standing of the community. The study highlights the methods of knowledge transfer, the innovation process, and the resultant economic benefits. The CSR initiative involved a session of workshops and continuous mentorship to ensure the sustainability of soap production within the community. By leveraging local resources and providing technical training, the project empowered community members to create a new source of income while addressing environmental concerns related to waste disposal. The paper also discusses the cooperative model adopted by the community, which facilitated resource sharing and collective problem-solving. The findings suggest that such CSR initiatives can significantly contribute to sustainable community development, economic empowerment, and environmental sustainability. The project's success demonstrates the potential of knowledge transfer to foster innovation and economic resilience in marginalized communities. Future research and similar projects could further explore the scalability and long-term impacts of these initiatives in other indigenous communities.